Planejamento e desenvolvimento de carreira: um estudo da relação UNIMINAS e seus discentes - Bernardes, Thays de Rezende Neves (2006)
This dissertation studied how business schools and students deal their professional careers. Thus, this study objective was doing a research that provides answers for the question: how Uniminas Administration Course and the students deal with career planning according with the professional market necessities and opportunities? In order to do that an applied and descriptive research, which tried analyze facts and phenomena characteristics that influenced the career planning of Uniminas Administration Course students. The technical procedures used were the bibliographical research, documental research and case study. The techniques involved interviews with the coordinator and the coordination support core professors; questionnaires applied to the students to trace the student profile and the most evident points which intervenes in their careers. The research typology was case study, a strategy for exam a contemporary phenomena inside the context it happens. Therefore, the efforts were conducted in order to identify the research variables which intervene and interact in career planning and developing programs, related to perceptions of people pertaining to initial research corpus. Inside the research line Strategy and Organizational Change the subject detaches for recognize and analyze the career planning impacts in human resource management, besides standing out its importance in the conception and longevity of Administration courses. The research results indicate that Uniminas deal with its students career planning and developing by the management of its curricular grade, working in activities and programs which support the students formation and helps them to know better themselves. Moreover, this organization maintains a healthy relation with local companies, and this approach the egress profile to market demands. The results to the question "how the student manage his career?" points a superficial knowledge for the meaning of career and how its planning can be a great difference in the students professional future. The students declared they want ascension in its current job or conquering new positions in big companies, because they believe that companies offers better chances for professional developing. The level of students involvement in educational activities was relatively good, but is necessary improve the conscience about the relevance of their participation in these activities, to complete their formation as administrators. Course contributions and the effectiveness theory concepts utilization in professional routine also helps to approximate the subjects studied with market requirements. At last, the students has to know better the administrator career during the course, understand the career planning and structure their information in order to guide them when the course ended. The tolls to do that, they already have.